1995
DOI: 10.1007/bf03162041
|View full text |Cite
|
Sign up to set email alerts
|

EPR studies of weakly coupled oxomolybdenum (V) and low-spin iron (III) porphyrin centers

Abstract: Novel compounds containing two S = 1/2 coupled spin centers (Mo(V) and low spin Fe(III)) have been investigated in detail by X-and Q-band EPR spectroscopy, spectral simulation and molecular modelling calculations. For one system with a Mo-Fe distance of ~9.4 A the dominant dipolar coupling allows distinction among structures that are consistent with molecular modelling calculations. For the second system with a Mo-Fe of ~7.9 A the exchange interaction is dominant (0.5 < J < 3.0 GHz). These coupled systems are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For the averaging, two-dimensional pseudo-random numbers ε uniformly distributed in the unit square were used, , so that the vector is uniformly distributed on a unit sphere. Here The number of points were 2 13 (8192) and 2 14 (16384).…”
Section: Epr Simulationsmentioning
confidence: 99%
“…For the averaging, two-dimensional pseudo-random numbers ε uniformly distributed in the unit square were used, , so that the vector is uniformly distributed on a unit sphere. Here The number of points were 2 13 (8192) and 2 14 (16384).…”
Section: Epr Simulationsmentioning
confidence: 99%
“…At 77 K these molecules display nearly axial spectra due to the pseudo-3-fold axis imposed by the three nitrogen atoms (of the facially coordinated tris(3,5-dimethylpyrazolyl)borate ligand, L) and three oxygen atoms (one oxo oxygen and two from the catechol fragment). Insertion of a diamagnetic metal into the porphyrin core does not change the Mo(V) EPR spectrum . However, when a paramagnetic metal ion is inserted into the porphyrin core, the Mo(V) EPR spectra change dramatically.…”
Section: Resultsmentioning
confidence: 93%
“…From a detailed EPR investigation at multiple frequencies and simulation of the respective spectra, we concluded that, for 4 , where the metal centers are separated by ∼9.4 Å (as determined by computer modeling), the primary interaction is dipolar in nature. The observed spectra could be simulated by considering the intermetal interaction to be primarily dipolar in nature and allowing minor changes in the spectroscopic g values for the molybdenum center . The g values for the molybdenum center in the simulated spectrum of 1 were 1.968, 1.943, and 1.939 (compared to 1.970, 1.968, and 1.925 for LMoO(catechol)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations